(untitled) (Andamios, Revista de Investigación Social, 2014)
“The secret of theology is anthropology”, bluntly state the author of The Essence of Christianity. Feuerbach, with this lapidary sentence, separated from the typical criticism of religion philosophy of the Enlightenment. In this follows the specific thought of Hegel. Religion and, especially, the idea of God, is no longer a predominantly epistemological problem, but historical-anthropological. Feuerbach question is no longer, as Kant, “how prepositions a priori possible?” Or “how can religion be possible?” But simply following Hegel, phenomenologically, “What is religion?” And “what do you mean by God?”. Feuerbach, therefore, assessment of landing a secularized man, whose process started from the philosophy of Descartes. Hegel will crown the historical development which he said, “the rational is real and the real is rational”, unifying in symbiosis logical metaphysics, divine and human, God and man. Basically, as a consequence of modernity, the criticism of heaven also tornaba criticism of earth.